The Need of ESP Reading Materials for Accounting Students - Yelliza (Fakultas Sastra Universitas Ekasakti, 2025)
This study explored the specific needs of English for Specific Purposes (ESP) reading materials for accounting students. Since reading comprehension played a crucial role in understanding accounting texts, reports, and financial statements, the study aimed to identify which reading skills were most essential to support students’ academic and professional competence. A quantitative descriptive design was employed, and data were collected from students through a needs analysis questionnaire consisting of ten indicators of reading skills. The results showed that most of the identified reading skills, such as understanding accounting vocabulary, interpreting numerical data, recognizing text organization, and summarizing accounting information, were categorized as highly needed; with an overall mean score of 3.3. The highest mean scores (3.5) were found in identifying main ideas, recognizing text structure, and making connections between texts and accounting practice. These findings emphasized the importance of developing contextualized ESP reading materials that integrated authentic accounting texts and reflected students’ real academic and professional needs.